The Role of Audit Committees in Moderating Tax Planning, Deferred Tax, and Firm Size on Earnings Management: Evidence from Consumer Goods Companies (2019–2023) - Firmansyah Tandju; Ni Made Suwitri Parwati; Nina Yusnita Yamin; Andi Ainil Mufidah Tanra (Politeknik Ganesha Medan, 2025)
This study aims to reveal the essence of audit committees in relation to tax planning, deferred tax expense, and company size on earnings management in consumer goods companies listed on the Indonesia Stock Exchange during the period 2019-2023. Quantitative measurements were made by applying structural model equations through WarpPLS V.8.0 analysis on 19 companies that met Purposive Sampling, with a total of 95 data observations for primary and non-primary consumer companies from 2019 to 2023. The study found that tax planning, tax expenses, and company size have a significant negative relationship with corporate earnings management practices, with an R-Square value of 22.6%, indicating the existence of a good earnings management prevention strategy in the research variable relationship. Tax planning (?=-0.390, p<0.001) suppresses earnings management, deferred tax expenses (?=-0.290, p<0.001) suppress earnings management, and company size (?=-0.562, p<0.001) suppresses earnings management. The audit committee plays an important role in strengthening the relationship between tax planning (?=-0.215, p<0.001) and company size (?=-0.366, p=0.003) in inhibiting corporate earnings management tendencies. However, in the case of deferred tax expenses (?=0.559, p<0.001), the audit committee allows earnings management to occur due to complexities and temporary differences that can become loopholes for management to commit fraud. This study provides insights into the comprehensive strengthening of corporate financial reporting oversight to avoid conflicts of interest between principals and agents, thereby maximizing corporate performance through corporate governance.